Malay Language Translation and Validation of the Seven-item Eustachian Tube Dysfunction Questionnaire [ETDQ-7(M)] - Tan, Heng Yao; Abdullah, Asma; Afandi , Ahmad Nordin; Hashim, Noor Dina (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Eustachian tube dysfunction (ETD) is commonly left unidentified, and clinicians often had to deal with its consequences. Hence, ETD symptoms should be routinely explored to unmask the diagnosis. The seven-item Eustachian Tube Dysfunction Questionnaire (ETDQ-7) is a user-friendly and disease-specific instrument introduced by McCoul et al. to assess the severity of ETD symptoms and treatment effectiveness. However, there is no Malay version of ETDQ-7 [ETDQ-7(M)] available for local population. This study aims to translate and validate the ETDQ-7 in Malay language. MATERIALS AND METHODS: The ETDQ-7 was translated and culturally adapted into Malay language. 68 adult patients with ETD and 68 healthy patients who served as control completed ETDQ-7(M). It was repeated on patients with ETD after two weeks. Statistical analysis was performed to determine the psychometric properties of ETDQ-7(M). RESULTS: ETDQ-7(M) displayed excellent internal consistency (Cronbach’s α = 0.93) which is comparable to the original questionnaire. There was excellent test-retest reliability (r= 0.86 – 0.99). No significant difference in total scores was observed between the first and second evaluations. The mean total score for patients with ETD and control group was 25.8 and 8.4 respectively. Discrimination between ETD and control group using a cut-off point of 13.5, yielded sensitivity and specificity of 100% respectively (area under curve=100%). CONCLUSION: ETDQ-7(M) is a validated questionnaire recommended for use in the management of ETD as a diagnostic tool and in treatment monitoring with excellent reliability and validity.